2015
DOI: 10.1016/j.biomaterials.2014.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Linking the foreign body response and protein adsorption to PEG-based hydrogels using proteomics

Abstract: Poly(ethylene glycol) (PEG) hydrogels with their highly tunable properties are promising implantable materials, but as with all non-biological materials, they elicit a foreign body response (FBR). Recent studies, however, have shown that incorporating the oligopeptide RGD into PEG hydrogels reduces the FBR. To better understand the mechanisms involved and the role of RGD in mediating the FBR, PEG, PEG-RGD and PEG-RDG hydrogels were investigated. After a 28-day subcutaneous implantation in mice, a thinner and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
144
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(147 citation statements)
references
References 67 publications
(77 reference statements)
3
144
0
Order By: Relevance
“…Only a few studies have looked specifically at the response of macrophages to hydrogels 23 . Gelatin methacryloyl (GelMA) hydrogels are becoming increasingly popular as they combine the bioactivity of gelatin with the tunability of a photo-crosslinkable hydrogel 19,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have looked specifically at the response of macrophages to hydrogels 23 . Gelatin methacryloyl (GelMA) hydrogels are becoming increasingly popular as they combine the bioactivity of gelatin with the tunability of a photo-crosslinkable hydrogel 19,24 .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a series of studies show that implantation of PEG hydrogels in vivo resulted in a more robust inflammatory response, characterized by a thicker fibrous capsule around the hydrogel, compared to PEG-RGD hydrogels [28]. Murine macrophages seeded on PEG hydrogels showed higher expression of IL-1β and TNF-α [28, 29] and PEG hydrogels adsorbed more serum proteins related to acute inflammation than PEG-RGD hydrogels [31]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that PEG hydrogels can activate serum complement proteins, leading to subsequent immune cell recognition [31]. Monodispersed and highly concentrated PEG polymers ranging from 2K to 11K [33], PEG 5000 stabilized carbon-nanotubes [34] and lipid-PLGA-PEG nanoparticles [35] were shown to generate complement activation when incubated with human serum.…”
Section: Discussionmentioning
confidence: 99%
“…[277] Amongst peptides of interest the cell adhesion properties of the RGD peptide have been particularly exploited in material functionalization. RGD is the smallest fibronectin-derived sequence that retains its cell-binding ability and is recognized by multiple cell-bound integrins, [278] leading to enhanced cellular adhesion on functionalized surfaces, [279] a reduced foreign body response [280] and, in some cases, increased cellular migration. RGD has been utilized to seed a poly(methylpentene) membrane with lung endothelial cells to create a bioartificial lung [281] and to promote short-term adhesion, proliferation and differentiation of neural stem cells on polyester materials, albeit less effectively than (laminin-derived) IKVAV in the latter case.…”
Section: Peptides In Surface Functionalizationmentioning
confidence: 99%